Teknik dan Metode Penerjemahan Istilah Artistik Dalam manga Nodame Cantabile Volume 1- 25 Karya Tomoko Ninomiya - Eka Suwari Dewi, Ni Putu; Anggraeny, Renny (Humanis, 2018)
This research, entitled “ T ranslations t echnique and methods of artistic terms on manga Nodame Cantabile Volume 1-25 by Tomoko Ninomiya”, used the theory of translation techniques by Molina and Albir (2002), theory of translation methodes by Newmark (1988) and componential analysis by Nida and Taber (1969). Based on analysis result , there are 126 data of artistic terms. According to 18 translation techniques by Molina and Albir , 12 techniques were used for translate artistic terms on manga Nodame Cantabile Volume 1-25 by Tomoko Ninomiya, namely  adaptation, amplification, borrowing, description, discursive creatios, generalization, linguistics amplification,  linguistics compression, literal translation, calque, established equivalent, and transpotition . T he data was also analyzed to determine the method of translation. Translation method that was used in this research is literal translation by Newmark (1988). From 126 data, there are 10 dat a caused the shift of meaning of artistic terms that analyzed by the theory of Nida and Taber (1969).